Growth, nutrient uptake and symbiosis with rhizobia and arbuscular mycorrhizal fungi in Lotus tenuis plants fertilized with different phosphate sources and inoculated with the phosphate-solubilizing bacterium Pantoea eucalypti M91 - Castagno, Luis Nazareno (2014)
Background and aims: The aim of this work was to evaluate the ability of P fertilization and phosphate-solubilizing bacteria (PSB) inoculation to promote the growth of L. tenuis in typical soils of the Salado River Basin (Argentina) with low P availability. Methods: Aboveground biomass and P and N levels were evaluated in field-grown L. tenuis plants inoculated with Pantoea eucalypti M91, either without fertilization or in combination with phosphate rock and triple superphosphate (TSP). The impact of P fertilization and inoculation on the symbiotic interactions between L. tenuis and native rhizobia bacteria and arbuscular mycorrhizal fungi was also evaluated. Results: Inoculation with M91 increased the L. tenuis biomass production and P concentration in shoots, at an early stage of plant growth. The combined treatment of inoculation with M91 and TSP significantly increased the P and N content in shoots compared to non-inoculated plants, fertilized or not. P. eucalypti M91 was found to endophytically colonize roots and leaves of L. tenuis plants grown in vitro and also under field conditions. Conclusions: The results suggesting that inoculation of L. tenuis with the PSB such as P. eucalypti M91 strain might allow more efficient use of N and P and a more sustainable option for grasslands producers from the Salado River Basin, in order to reduce costs and avoid increased levels of P insoluble in soils.